Budget Deficits and Interest Rates : A Fresh Perspective - Aisen, Ari (IMF Working Papers; Working Paper ;, 2008)
We extend the literature on budget deficits and interest rates in three ways: we examine both advanced and emerging economies and for the first time a large emerging market panel; explore interactions to explain some of the heterogeneity in the literature; and apply system GMM. There is overall a highly significant positive effect of budget deficits on interest rates, but the effect depends on interaction terms and is only significant under one of several conditions: deficits are high, mostly domestically financed, or interact with high domestic debt; financial openness is low; interest rates are liberalized; or financial depth is low.